Neutron measurements and diagnostic developments relevant to fast ignition - Habara, H; Norreys, P; Kodama, R; Stoeckl, C; Glebov, V (2006)
In recent fast ignitor research, neutron measurements have become increasingly important not only to understand the ultraintense laser-plasma interaction physics associated with ion acceleration and energy transport processes in dense plasmas but also the characterization of the plasma temperature in integrated experiments, as summarized in this paper. New technologies that are relevant to the next-generation integrated fast ignition experiments are also reviewed. These will become increasingly important in the next few years as second-generation multikilojoule petawatt facilities come online and the detection environment becomes increasingly hostile, particularly if, as anticipated, the generated neutron fluxes begin to approach energy breakeven conditions.